The Effectiveness of Online Nutrition Counseling on Fish and Protein Consumption to Prevent Stunting in Children Aged 4-6 Years - Lusyta Puri Ardhiyanti; Diah Ratnawati (Borneo Scientific Publishing, 2026)
Stunting remains a significant public health problem in Indonesia, and inadequate fish and protein intake among preschool children is a key modifiable risk factor. The use of Zoom- and telephone-based nutritional counseling represents a novel, accessible strategy for community-based dietary education, yet evidence on its effectiveness in the Posyandu setting remains limited. This study aimed to evaluate the effect of nutritional counseling delivered through Zoom meetings and telephone communication on fish consumption and protein intake among children aged 4–6 years. A quasi-experimental one-group pretest–posttest design was employed at Posyandu Rajawali 1 and 2, Tugu Village, Depok, West Java. All 22 eligible children were included using total sampling. Mothers served as respondents. Dietary intake was assessed using 24-hour dietary recall and food frequency questionnaires over three non-consecutive days, administered before and after three educational sessions held in April–May 2025. Paired t-test was used for bivariate analysis. The results of the study show that mean fish consumption increased significantly from 23.91 g to 30.68 g (Δ = 6.77 g; p = 0.0001) and mean protein intake from 30.94 g to 38.45 g (Δ = 7.51 g; p = 0.0001). In conclusions, zoom and telephone-based nutritional counseling was associated with significant short-term improvements in fish and protein intake. However, given the absence of a control group and small sample size, causal inference is limited. Post-intervention intake levels remained below recommendations, suggesting the need for complementary structural and repeated educational interventions. Future studies with larger samples, control groups, and anthropometric outcome measures are strongly recommended.